Meningkatkan Hasil Belajar IPA Melalui Model Problem Based Learning (PBL) pada Siswa Kelas VI SDN Burangkeng 02 Kecamatan Setu Bekasi - Puspitasari, Tirta (Journal of Contemporary Issue in Elementary Education, 2024)
This research was motivated by the low results of science learning on puberty material in class VI students at SDN Burangkeng 02, Setu District, Kab. Bekasi. The aim of this research is to determine the improvement in science learning outcomes regarding puberty through the Problem Based Learning model. This type of research uses Classroom Action Research (PTK) with planning, implementation, observation and reflection steps. This PTK is carried out in two cycles. Cycle I was carried out on 03 April 2023 and Cycle II was carried out on 04 May 2023. The research was carried out in class VI at SDN Burangkeng 02, Setu District, Kab. Bekasi with a total of 20 students consisting of 6 men and 14 women. Based on the conclusions of the research results, it shows that the Problem Based Learning (PBL) model can improve science learning outcomes for puberty material in class VI students at SDN Burangkeng 02, Setu District, Kab. Bekasi. The increase in science learning outcomes in building materials is known from the test results in Cycle I and Cycle II which show an increase in the average score and percentage of classical completion. The average student score for spatial construction material in the initial condition (pre-cycle) was 69 with classical completeness of 40% (8 students) out of 20 students who achieved a score ≥ 75 (KKM score). In cycle I, a score of 74 was obtained with classical completeness of 60% (12 students) achieving a score of ≥ 75 (KKM score). Cycle II obtained a score of 81 with classical completeness of 80% (16 students) which achieved a score of ≥ 60 (KKM score).